KEIKUTSERTAAN MASYARAKAT DALAM INVESTASI FUTURE ECOMMERCE (FEC): SEBUAH ANALISIS DARI PERSPEKTIF HUKUM ISLAM: STUDI KASUS DI GERUNG KABUPATEN LOMBOK BARAT - Karmaen, Samsul (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2025)
This research is motivated by the widespread participation of the community in investing in the Future E-Commerce/FEC application. The high level of public interest in this investment is due to the ease of the method and the potential for large profits offered in a short time. In using the Future ECommerce/FEC application, investors act as third parties, who are involved in product buying and selling activities with capital provided by third parties. The type of research used is field research, with qualitative research methods. The data sources used include primary and secondary data, with data collection techniques through interviews and documentation. The results of the study indicate that investment practices in the Future E-Commerce/FEC application in Gerung are not in accordance with Islamic law. Due to violations of the principles of agreement in Islamic Law, the provider of the Future ECommerce/FEC application is considered to have committed a breach of contract against investors because the promises offered do not match what was agreed.